Perception study interpersonal relationships in sports psychology (The Journal of Psychology and Sociology, 2017)
This article analyzes the sport activities of the different psychological approaches. It describes the perception of interpersonal relationships between coaches and athletes from the perspective of sports psychology. In general, developed theoretical apparatus of scientific research challenges the perception of the relationship and its impact on sports activities. This problem is considered in the framework of cognitive, personality - and the activity of other approaches. When student-activity approach to the organization of research are opportunities to identify common psychological patterns inherent in different activities related to the athlete’s personal characteristics. Its essence lies in the fact that the sport is not seen as a means of formation and development of knowledge, skills, ie experience, but as a way of development of the individual athlete. Also the situations of sports activities from the perspective of the coach and athlete, which affect the development of sporting qualities and performance makes the analysis of psychological features of the exchange of information between the coach and athlete and compare sports awareness of the situation from the perspective of athletes and coaches. Joint activities creates the possibility of the formulation of a common goal, direct personal contact between the actors. Theoretical number analysis the perception of interpersonal relationships between coach and athlete gives the main categories of information elements, which are formed due to the perception of sports activities. Thus, it was found that certain categories are more important and play a major role in interpersonal relationships between coaches and athletes in the perception of sports activities. Among these technical elements, psychological condition of the athlete and organizational factors as information elements. Various types of awareness in various sporting situation were identified. Also, the relation of individuals to a particular type of personality, as well as type of temperament, are estimates in the analysis of interactions of subjects in the subsystem “coach-athlete” in an incomplete measure.Key words: sports activities, the perception of interpersonal relationships, interpersonal relationship between coach and athlete.